Głos Solidarności . dwutygodnik Regionalnej Komisji Organizacyjnej NSZZ "Solidarność" Ziemi Łódzkiej, no. 22, 1989 - Ciechanowicz-, Sarata, Aleksandra; Lipski, Paweł; Wiśniewski, Walerian; Drewnicz, Dariusz; Marszal, Krzysztof; Mirecki, Tadeusz (RKO NSZZ "S", 1989)
Creation and circulation: For trade-union use